Different effects of bronchoscopic interventions on children and adults with tracheobronchial mucoepidermoid carcinoma. Issue 2 (April 2022) - Jieli, Zhang; Yunzhi, Zhou; Nan, Zhang; Heng, Zou; Hongwu, Wang; Jiankun, Liu; Dongmei, Li; Hui, Wang; Jing, Lv; Changxin, Li; Mao, Jiangfeng
Aims: To investigate the efficacy and safety of minimally invasive bronchoscopic interventions for patients with tracheobronchial mucoepidermoid carcinoma (MEC). Methods: Patients with tracheobronchial MEC were included in this retrospective study, and the clinical features, histologic grading, treatments, and cumulative survival rates were calculated. Patients were categorized into child (n = 16) and adult (n = 19) group according to their ages. Histologic grading, treatments, and survival status were compared between the two groups. Results: In pathology, high-grade MEC counts for 6.77% and 42.10% in the child and adult group, respectively. As tumor growth pattern was concerned, 93.33% and 21.05% tumors in the child and adult group present intratracheal type. Multiple bronchoscopic interventions were conducted, including rigid bronchoscopy, argon plasma coagulation (APC), dioxide carbon cryotherapy, and electric loop. Tumors could be removed by multiple bronchoscopic interventions. Bronchoscopy-associated complications were rare, including an oral mucosa injury and a glottis edema. In the child group, one patient underwent left upper lung lobectomy. In the adult group, lobectomy and/or chemotherapy and/or radiotherapy were conducted in seven patients. The 5-year survival rate was 100% and 68.90% in the child and the adult group, respectively. Conclusions: Almost all children have low-grade and intratracheal MEC; 2/5 adults have invasive high-grade MEC. Multiple bronchoscopic interventions are effective in erasing low-grade intratracheal MEC without severe complications. For high-grade invasive MEC, aggressive and comprehensive therapy should be considered.